2015
DOI: 10.1007/s12013-014-0450-2
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of miRNA-21 Sensitizes Human Gastric Cancer Cells to Paclitaxel

Abstract: The development of drug resistance has largely limited the clinical outcome of anti-cancer treatment. Recent work has highlighted the involvement of non-coding RNAs, microRNAs (miRNAs), in cancer development. The present study aimed to investigate the role of miR-21 in the development of drug resistance to paclitaxel in gastric cancer cells. Our study found that the expression of miR-21 upregulated in the paclitaxel resistant cell line SGC7901/paclitaxel compared to its parental line SGC7901. Moreover, over-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Treatment with miR-21 mimics resulted in increased expression levels of P-gp in wild-type SGC7901 cells, whereas treatment with miR-21 inhibitors showed decreased levels of ABCB1 mRNA and P-gp protein expression in the SGC7901/PTX cells. Therefore, given the modulating effect of miR-21 on PTX sensitivity, these results suggest that miR-21 might work via regulating somehow the P-gp expression, which is involved in PTX resistance in SGC7901/PTX cell lines [ 49 ].…”
Section: Micrornas As Regulators Of Drug Resistance Pathways In Gcmentioning
confidence: 99%
“…Treatment with miR-21 mimics resulted in increased expression levels of P-gp in wild-type SGC7901 cells, whereas treatment with miR-21 inhibitors showed decreased levels of ABCB1 mRNA and P-gp protein expression in the SGC7901/PTX cells. Therefore, given the modulating effect of miR-21 on PTX sensitivity, these results suggest that miR-21 might work via regulating somehow the P-gp expression, which is involved in PTX resistance in SGC7901/PTX cell lines [ 49 ].…”
Section: Micrornas As Regulators Of Drug Resistance Pathways In Gcmentioning
confidence: 99%
“…As shown in Table 3, limited studies have been conducted to investigate the roles of miRNAs in the resistance mechanisms to other chemotherapy drugs. MiR-155-5p, miR-34c-5p, and miR-21 were found to be related to PTX resistance; [65][66][67] miR-361-3p, miR-135a, and miR-27a affect OXA resistance; [68][69][70] miR-1284 and miR-647 regulated VCR resistance; 71,72 and miR-200a inhibited taxol resistance, while miR-361-5p suppressed docetaxel Notes: *Targets genes were confirmed by Western blotting, RT-qPCR or dual-luciferase. **Upregulation (↑) or downregulation (↓) of miRNAs enhance chemosensitivity.…”
Section: Other Single-drug Resistancementioning
confidence: 98%
“…30,48,64 Other studies showed that miR-21 targets P-gp to induce PTX resistance. 65 Notably, PTEN is not only a target gene of miR-21-5p but is also a target of miR-193-3p, miR-147, and miR-106a. 21,22,46 Through targeting PTEN, miRNAs regulate 5-FU, DDP, and DOX resistance in GC.…”
Section: Other Single-drug Resistancementioning
confidence: 99%
“…A significantly elevated miR-21 expression was observed in PTX resistant SGC7901/PTX gastric cancer cells compared to the parent SGC7901 cells. MiR-21 could dramatically inhibit apoptosis induced by PTX, partly through regulating P-gp expression [143]. MiR-23a, which is dramatically up-regulated in human gastric cancer tissues, has been shown to weaken PTX-induced apoptosis and accelerate proliferation of BGC823 and MGC803 gastric cancer cells via suppressing expression of interferon regulator factor 1 (IRF1) [144].…”
Section: Mirnas and Ptx Resistancementioning
confidence: 99%